Post-Learning Cycle, a Web-Based Formative Assessment Model on Physics Learning Temperature and Heat Matter - Ediyanto Ediyanto (Journal of Disruptive Learning Innovation (JODLI), 2020)
Web-based formative assessment model in the current study divided into three cycles of a pre-learning cycle, learning cycle, and post-learning cycle. Previous research in the pre-learning stage, web-based formative assessment models can provide feedback quickly and can improve students' understanding of concepts. The current study develops the post-learning cycle, a web-based formative assessment model in physics specifically for heat and temperature materials in vocational school students grade X. The present study is used in the research and development method. Post-learning cycle, a web-based formative assessment model developed with six stages: 1) the collection of information and drafting, 2) planning, 3) establish initial product, 4) validate the initial product, 5) revisions, and 6) trial in the field. As a result, the post-learning cycle, a Web-Based formative assessment model is divided into three stages: diagnostic test, recording, and feedback. Based on trial results, it was found that the post-learning cycle, a web-based formative assessment model can help teachers and students to get quick feedback. Rapid feedback can help students to gain an understanding of the concept quickly and can help teachers to find students so that problems can be solved promptly. This formative assessment model can be used as a tool for assessment and evaluation of the achievement of student learning outcomes. In the future, a post-learning cycle, a Web-Based formative assessment model, can be used for learning other than physics.